GEOLOGICAL AND GEOTECHNICAL INVESTIGATIONS OF GALI ZAKHO TUNNEL, DUHOK, KURDISTAN REGION – IRAQ - MOHAMMED, JAAFAR A. (Journal of Duhok University, 2023)
Geographically, northern Iraq, specifically on the border between Iraq, Turkey, and Iran, is considered a complex geological area consisting of different types of rocks, including sedimentary, igneous, and metamorphic. The height of the mountains in these areas ranges between 2,000 and 4,000 meters. Recently, many changes occurred in the region as a result of natural disasters such as earthquakes, random drilling of wells, and the rapid development of multi-story buildings, which led to many modifications in the geology of the Kurdistan Region. In order to construct any tunnel, the geological plan and profiles should be formed by evaluating the site investigations, and the boreholes should be drilled through the tunnel route. Accurate investigations about the geological structure and nature of the ground can be conducted during the excavation. Also, essential laboratory tests are done on core samples extracted from boreholes along the tunnel. The behaviors of the geological and geotechnical situation of the tunnel are presented, focused on the inlet of the tunnel. This work relied on previous geological investigation surveys that were conducted in the region and related to this subject, the results of geological field mapping and laboratory tests, and the geological and geotechnical parameters used for the design and construction of the tunnel. The best excavation method that can be used in this area is the New Austrian Tunneling Method (NATM), based on the economic and area conditions.